Phylogeny and identification of Pantoea species causing leaf blight disease of rice in Peninsular Malaysia - Azizi, Mohammad Malek Faizal; Mohamed Zulperi, Dzarifah; Ismail, Siti Izera; Mohd Hata, Erneeza; Md Yasin, Ina Salwany; Abdullah, Mohd Amir Fursan (Faculty of Agriculture, Universiti Putra Malaysia, 2018)
Leaf blight is a severe disease of rice as it losses the quality of rice production, hence affecting the economic development of rice production in Malaysia. Symptoms of leaf blight appeared as water-soaking lesions from upper part of the leaf blades and later turned into brown stripes. The disease is commonly known to be caused by Xanthomonas oryzae pv. oryzae. In this study, strains isolated from exhibiting leaf blight symptoms in infected rice fields located in Kedah and Selangor were confirmed to be caused by Pantoea ananatis and Pantoea stewartii, based on the cultural characteristics and phylogenetic analysis. Phylogenetic analysis constructed by using MEGA 7 software of gyrb gene sequence from 26 Pantoea genome delineated the clustering of eight strains into Pantoea stewartii ARC 229 reference strain (GenBank accession number KX342015) and 30 strains into Pantoea ananatis ARC60 reference strain (GenBank accession number KX385187), both with 99% sequence similarity. These findings may aid in the understanding of the generic relationship of Pantoea stewartii and Pantoea ananatis causing leaf blight disease of rice in Peninsular Malaysia.